Analisis Konsep New Urbanism Dan Dampak Pada Perilaku Mobilitas Masyarakat Perkotaan di Indonesia - Aisiyah Nur Rahmawati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
In recent years, one of the urbanism phenomena that has occurred in Indonesia is the existence of villages located in urban centers. Urban mobility is the most critical challenge encountered in various cities. The frequent occurrence of traffic jams, air pollution, and people's dependence on using private transportation rather than public transportation is a challenge to urban mobility that requires sustainable solutions. The concept of new urbanism can be used as a way to approach urban planning to overcome problems that are related to urban design. One of the cities in Surabaya that applies the concept of new urbanism is Jambangan Village, where the dominant community has implemented several indicators of Asian New Urbanism to become a sustainable village. The aim of this research was to explain the concept of new urbanism implemented in cities in Indonesia and to analyze the impact of implementing new urbanism on the mobility behavior of urban communities in Indonesia. The research taken in this journal is qualitative research with the research approach used, namely a library research approach. This approach prioritizes reviews of the literature by collecting data from various sources. The existence of the new urbanism concept can have a positive impact on Jambangan Village if it is handled appropriately.